The Impact of Erectile Dysfunction on Quality of Life and Mental Health in Men - Hobot, Jakub; Iwanicki, Michał; Hobot, Maciej (Quality in Sport, 2026)
Erectile dysfunction (ED) is a prevalent and multifactorial condition that affects men worldwide, with vascular, hormonal, neurological, and psychological factors contributing to its development. Beyond impairing sexual performance, ED has significant consequences for mental health, quality of life, and interpersonal relationships, and may serve as an early indicator of systemic diseases such as cardiovascular disease and metabolic syndrome. Men with ED frequently experience depression, anxiety, reduced self-esteem, and relational difficulties, highlighting the importance of evaluating both psychological and physical health in this population. Effective management includes pharmacological interventions such as sildenafil or tadalafil, psychosexual therapy, and lifestyle modifications, all of which can improve erectile function as well as psychological well-being. A holistic, multidisciplinary approach involving primary care physicians, urologists, and mental health professionals is essential to optimize outcomes and address both the physiological and psychosocial aspects of ED. Recognizing ED as a multidimensional condition underscores the need for comprehensive assessment and integrated care strategies to enhance quality of life and overall health in affected men.